ANALYSIS OF TOP DESTINATIONS IN TOURISM, ACCORDING TO VOLUME OF RECEIPTS DURING 2001-2011 - Alexandru FÎNTÎNERU; Gina FÎNTÎNERU; Dragoș-Ion SMEDESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2014)
More significantly, tourism has emerged as a distinct and definite branch in national economies of many countries,being a pleasant way to pass the free time, has engaged in providing services in various fields adjacent to.Characterized by mobility and adapt to the requirements of demand and supply, it is from this point of view the mostdynamic sector and, all at once, the most important generator of jobs, acting as a global economic system moredynamic, involving and stimulating the production of other areas. The paper aimed is to analyze the top tendestination in tourism, by volume of receipts, during 2001-2011, plus Hungary, Bulgaria and Romania, accordingto Data World Bank, from 172 countries, when global tourism, has evidenced by the following amounts: 1.256 billion $ in tourism receipts in 2011 to 563 billion $ in 2001 and about 1 billion tourist arrivals recorded at end of 2011, compared to 680 million tourist arrivals in 2001.